The synthesis and the two scenarios. (13th January 2022) - Beatty, John
Abstract: On the occasion of the 75th anniversary of the Society for the Study of Evolution, I look back at the so‐called "evolutionary synthesis, " to which many of the Society's founders and prominent founding members were committed. An important plank in the synthesis platform had to do with the importance of selection relative to mutation. Of course, there is no evolutionary change without mutation, and no adaptive evolutionary change without selection. So how could selection be more important than mutation, or vice‐versa? At issue was whether adaptive evolutionary change is initiated and directed by selection, or by the appearance of new advantageous variation. Proponents of the synthesis took the position that Darwin himself had defended, namely that adaptive evolutionary change is initiated and directed by natural selection on standing variation, no new variation, no mutation, required . Natural selection is, in this sense, not just "creative, " but is the creative agent of evolutionary change. In taking this extreme position, proponents of the synthesis were reacting to the equally extreme position of Mendelian‐mutationists, who held that adaptive evolutionary change always commences with, and is directed by, the appearance of new advantageous mutations, and for whom mutation is the creative agent of evolutionary change. I conclude with some comments on "relative significance" issues and controversies, and respects in which the relative significance issues at the heart of the synthesis persist.